Contemporary theories of teaching religion. Between tradition and modernity - Michalski, Jarosław T. (Forum Pedagogiczne, 2020)
The author attempted to present the following main theories of teaching religion: the theory of personality, theory of authenticity, theory of testimony, theory of the Holy Spirit, dialogue theory, proclamation theory and teaching theory. All of the theories with their obvious advantages, claim the broadly understood theory of teaching to be the most useful in the practical activities. The teaching theory contains the most important elements of other theories. It has a huge potential for explanation, thus becoming the essence of all theories of teaching religion. It ultimately determines the most effective model of practical activities that make up the process of modern religion teaching. This article refers directly to the paradigm of the theoretical teaching of religion and religious knowledge, while indirectly to the other paradigms, because the theory of teaching religion (like any other teaching theory) determines the type and quality of its practice.